Acute Heart Failure Exacerbation with Cardiogenic Shock and Elevated Systemic Vascular Resistance Treated with a Combination of Nicardipine and Dobutamine Therapy - Lydia E. Issac; Setri Fugar; Naser Yamani; Burhan Mohamedali (Case Reports in Cardiology)
Acute heart failure is a common reason for hospital admission and is usually caused by decreased cardiac output either as a result of an intrinsic cardiac issue or as a result of severe hypertension with elevated afterload. We present a patient with a history of HFrEF who presented with acute heart failure, found to have hypotension requiring Dobutamine support and an elevated systemic vascular resistance requiring Nicardipine drip, with subsequent recovery of cardiac function.